Pengaruh Layanan Administrasi Kesiswaan Terhadap Kepuasan Peserta Didik di MA Madinatunnajah Ciputat - Makhfudhoh Alfiani Fauziah; Abdul Aziz Hasibuan; Lolytasari Lolytasari (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2022)
One of the factors that causes the low quality of education is in the process of providing educational services that still does not meet expectations. Educational customers (students) are entitled to a worthy and appropriate educational service to their expectations during their education in educational institution. Therefore, educational institutions should be able to find the solution in improving services to meet the needs of students. The study aims to analyze how the student’s administration services affect the student satisfaction. The author uses a quantitative method. Based on the results, regression coefficient value of 0,495 shows positive value. The value of t-count obtained is 17,195 > t-table 1,973 with significance value of 0,000 < 0,05. The value of R Square 0,627 and the coefficient determinations value is 62,7%. Thus, there is significant effect between the student’s administration services on the student satisfaction. Keywords: Student administration, student satisfaction, and boarding school administration.